Parliamentary ombudsman survey 1964-1972 - Strömberg, Lars (University of Gothenburg, 1983)
The purpose of the study is to illustrate various aspects of the Ombudsman's work, who complains, what is complained about, whom is complained against, which investigative measures are taken, how long time the handling takes and what decision the Ombudsman has taken.

The purpose of the study is to illustrate various aspects of the Ombudsman's work, who complains, what is complained about, whom is complained against, which investigative measures are taken, how long time the handling takes and what decision the Ombudsman has taken.
JO-undersökningen 1964-1972
Keywords: internal politics; inrikespolitik; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap